A Case Study Exploring the Influence of a Gardening Therapy Group on Well-Being. (2nd April 2016) - Joyce, Jenny; Warren, Alison
ABSTRACT: In a climate of improving health-care quality and understanding, this study explored how participation in a gardening group, facilitated through a mental health service in Ireland, influenced well-being. A case study used semi-structured interviews and participant observation to explore explicit and tacit aspects of group participation. Thematic analysis clarified that gardening group participation had a positive influence on well-being for all gardeners and group facilitators. This was through promoting coping, facilitating change, and developing skills. The setting, site ethos and tasks were important in assisting people to make lifestyle changes and to develop skills in order to experience well-being.